Realme Smartphone Purchase Decisions are Reviewed From Lifestyle, Product Quality and Suitability Prices In Way Kanan - Ida Bagus Nyoman Udayana; Hutami, Lusia Tria Hatmanti; Khunaini, Muhammad Romadon (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
The purchase decision is a consideration of a person assessing different options and determining the product from many possibilities. The purpose of this study is to determine the influence of lifestyle, product quality, price suitability on realme smartphone purchase decisions. The study was conducted in Way Kanan Regency by distributing questionnaires to a sample of 100 respondents through probability sampling techniques. Data was analyzed using SPSS 24. Analytical techniques in this study use descriptive analysis, data quality test, classical assumption test, multiple linear regression test, hypothesis testing. The results of this study showed that lifestyle variables influenced purchasing decisions with a significance value of 0.037. The significance value of the product quality variable influencing the purchase decision is 0.009. The price risk variable influences purchasing decisions with a significance value of 0.004. Lifestyle, product quality, and price-related variables influence purchasing decisions with a significance value of 0.000